Una visión panorámica de los estudios antropológicos sobre Timor-Leste desde 2002: veinte años de antropología en un país soberano - Fidalgo-Castro, Alberto (El Colegio de México, 2022)
Professional anthropological research in Timor-Leste, which started during the final years of Portuguese colonial rule, came to a halt after the Indonesian occupation. During this period, anthropological studies were mostly carried out under close supervision of the Indonesian state itself, mostly with the goal of ultimately legitimizing the occupation. With the restoration of independence and the return of sovereignty, there was a resurgence of anthropological studies which initially focused on work oriented to the design of reconstruction and development policies, as well as human rights. As the years have passed and with waning interest in Timor-Leste as a country reopened to research, other areas of study have emerged. This article surveys different research projects undertaken during the last twenty years of anthropological work in the country.